Evaluation of the splint-supported Forsus Fatigue Resistant Device in skeletal Class II growing subjects - Elkordy, Sherif A.; Abdeldayem, Ramy; Fayed, Mona M. S.; Negm, Ibrahim; El Ghoul, Dina; Abouelezz, Amr M. (The Angle orthodontist, 2021)
To evaluate the use of the Forsus Fatigue Resistant Device (FFRD), supported with bimaxillary splints, in treatment of skeletal Class II malocclusion. Data from 46 skeletal Class II females who received either conventional Forsus alone (FFRD group) (15 patients, 12.54 ± 0.90 years), FFRD and bimaxillary splints (splint-FFRD group) (15 patients, 12.29 ± 0.82 years), or were untreated controls (16 subjects, 12.1 ± 0.9 years) were retrieved from previous clinical trials. FFRD was inserted onto the mandibular archwire in the FFRD group after leveling and alignment with multibracket appliances. In the splint-FFRD group, Forsus was inserted between fixed maxillary and mandibular splints. Treatment continued until reaching an edge-to-edge incisor relationship. Both treatment groups failed to induce significant mandibular skeletal effects compared to the normal growth exhibited by untreated controls. The splint-FFRD group showed significant reduction of SNA (-0.88° ± 0.51°) and ANB (-1.36° ± 0.87°). The mandibular incisors showed significant proclination in the FFRD (9.17° ± 2.42°) and splint-FFRD groups (7.06° ± 3.34°). The newly proposed splint-supported FFRD was equally effective as the conventional FFRD in treatment of Class II malocclusion with dento-alveolar changes and additional maxillary restricting effect. It has an additional advantage of immediate initiation of the Class II correction.